Microbial profile and associated factors of external ocular bacterial and fungal infections in Arba Minch General Hospital: a cross-sectional study - Melat Woldemariam; Addis Aklilu; Aseer Manilal; Masresha Mengistu; Dagimawie Tadesse; Munira Siraj; Ashraf Atef Hatamleh; Bassam Khalid Alnafisi; Akbar Idhayadhulla (Scientific Reports)
Abstract External ocular infections are of serious global concern, which cause significant visual morbidity and even blindness, particularly in low-income and resource-limited countries. Herewith, we are reporting the profile of bacteria and fungi causing external ocular infections and the associated factors in Arba Minch, southern Ethiopia. An institution-based cross-sectional study was conducted among 259 suspected individuals with external ocular infections from 01 January to 10 June 2020 in Arba Minch General Hospital. The demographic data were obtained using a structured questionnaire, while corneal scrapings and conjunctival swabs were collected for culture. Samples were inoculated onto MacConkey, blood, mannitol salt and Sabouraud dextrose agar plates. Bacteria were characterised using conventional microbiological techniques. Fungal isolates were identified by culture and morphology by means of microscopy. Antibiotic susceptibility tests for bacteria were performed via the Kirby-Bauer disk diffusion technique. A logistic regression analysis determined the association between dependent and independent variables; P values ≤ 0.05 were considered statistically significant. The most common clinical manifestations in culture-proven cases were conjunctivitis (38.6%, n = 100) and blepharoconjunctivitis (25.9%, n = 67). The overall prevalence of external ocular bacterial and fungal infections was 73.2 (n = 115) and 26.8% (n = 42), respectively. Isolates of Staphylococcus aureus (24.8%, n = 39) and Pseudomonas aeruginosa (13.4%, n = 21) were the predominant Gram-positive and Gram-negative bacteria, respectively. The prevalence of multidrug-resistant bacteria was 71.3% (n = 82). The World Health Organisation-prioritised bacteria such as methicillin-resistant S. aureus (61.5%, n = 24), extended-spectrum beta-lactamase (22.6%, n = 12), and carbapenemase-producing Enterobacteriaceae (15.1%, n = 8) were also detected. The prominent fungi recovered from patients with keratitis and conjunctivitis were Aspergillus spp. and Candida albicans, respectively (9.5%, n = 15 each). Age (26–49 years) and family income were statistically associated with ocular infections (P ≤ 0.05). The results provide insights into the characteristics of major ocular bacterial and fungal pathogens circulating in the ophthalmic patients of Arba Minch. Conjunctivitis is the main ocular manifestation observed, with a predominance of S. aureus. More than two-thirds of the ocular bacteria were MDR, and the highest prevalence corresponds to S. aureus. The aggravation of multi-drug resistance, including the WHO-prioritised ones, warrants periodic evaluations.